Information System for Drug Sales at Advent Hospital Medan - Hutahaean, Mian Natanael; Singarimbun, Roy Nuary; Purwawijaya, Ellanda (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
The management of drug sales data in hospitals plays a crucial role in ensuring operational efficiency and patient safety. However, the semi-manual process at Advent Hospital Pharmacy in Medan often leads to issues such as stock data inaccuracies and reporting delays, with a transaction error rate reaching 20%. This study aims to design and build a desktop-based drug sales information system using Microsoft Visual Basic.net to address these problems. The development method used is Research and Development (R&D) with a waterfall model, which includes the stages of requirements analysis, design, implementation, and testing. The system was evaluated through two approaches: a usability test with a questionnaire administered to 5 users and a black-box test with 13 functional scenarios. The results showed that the developed system achieved a usability score of 81%, which falls into the